2018
DOI: 10.1002/chem.201801328
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzofuranones via Malonates Desymmetrization: Yield Increase by the Portion‐wise Addition of Quinones

Abstract: The organocatalyzed addition of several malonates to 1,4-benzoquinones affords benzofuranones bearing a quaternary stereocenter with good enantioselectivity. This reaction is an intramolecular desymmetrization since it proceeds through the formation of an arylated achiral malonate that cyclizes to give the reaction product. The addition rate of the quinone dramatically affects the reaction yield which was originally low. The yield was considerably increased, in some cases, from less than 20 % to over 95 %, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Consequently, substantial endeavors have been devoted to this burgeoning domain during the last 5 years and a diverse number of novel desymmetric transformations have been successively exploited. Apart from aforementioned cases, other readily available substrates have been studied as well, such as diesters [101], acetals [102], and diamines [103,104]. These remarkable advances not only combine the respective advantages of organocatalysis with desymmetrization, which accelerates the development of related methodologies, but also open up new avenues for synthetic community.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, substantial endeavors have been devoted to this burgeoning domain during the last 5 years and a diverse number of novel desymmetric transformations have been successively exploited. Apart from aforementioned cases, other readily available substrates have been studied as well, such as diesters [101], acetals [102], and diamines [103,104]. These remarkable advances not only combine the respective advantages of organocatalysis with desymmetrization, which accelerates the development of related methodologies, but also open up new avenues for synthetic community.…”
Section: Discussionmentioning
confidence: 99%
“…The organocatalyzed coupling of malonates 66 with benzoquinones 65 affording enantioenriched benzofuranones 68 was reported by Salvio and Bella. 83 Interestingly, the yield of the cyclization reaction could be enhanced via the portion-wise addition of quinones rather than at once, maintaining similar enantioselectivity (up to 95 : 5 er). Differently substituted malonates (R 2 = Me, Et, Bn, n Pr, NHCOMe, etc. )…”
Section: Synthesis Of Fused Frameworkmentioning
confidence: 99%
“…In 2019, Bella, Salvio, and their co‐workers, in the course of their studies about enantioselective organocatalysis, reported an organocatalytic synthesis of benzazetidines starting from inexpensive materials, which does not require any additive based on transition metals, unlike the procedure recently reported and illustrated above . The starting materials of this preparation are isatin and its derivatives.…”
Section: Synthetic Approaches For the Synthesis Of Benzazetidinesmentioning
confidence: 99%